Agricultural Economic Resilience in the Context of International Food Price Fluctuation—An Empirical Analysis on the Main Grain–Producing Areas in Northeast China - Yang, Qifeng; Zhang, Pingyu; Ma, Zuopeng; Liu, Daqian; Guo, Yongjia (Sustainability, 2022)
In the context of international food price fluctuations, agricultural economic development is usually subject to large shocks, which also leads to clear spatial–temporal differentiation in regional agricultural economic resilience. However, there is a paucity of retrievable studies on the evolutionary process of agricultural economic resilience and its impact mechanisms. Taking the impact of and disturbance caused by international food price fluctuations on the agricultural economy from 2005 to 2021 as the research background, this paper adopts the economic resilience analysis framework and selects gross agricultural output value indicators to measure the agricultural economic resilience of 12 cities in the main grain-producing areas in Northeast China–Sanjiang Plain and Songnen Plain. At the same time, the regression model is used to further analyze the spatial and temporal changes of agricultural economic resilience and the main influencing factors. Based on the results of the research, it can be concluded that: ① international food prices exert different degrees of influence on agricultural economic resilience at different stages. From 2005 to 2013, the agricultural economic resilience of the two plains changed less, and the resilience capacity performed better in both the period of falling and rising international food prices, while from 2014 to 2021, the agricultural economic resilience of the two plains changed more due to the great impact of international food price fluctuations, with a steep decline in resilience capacity in the period of falling international food prices from 2014 to 2017, followed by a rapid rebound between 2018 and 2021. ② There are differences in the resilience capacity of the agricultural economy in the main maize- and rice-producing areas. Although it is a fact that agricultural economic development in the two major plains is faster than the national average in most periods, the comparison reveals that the main corn-producing area (Songnen Plain) is more volatile and its resilience capacity is relatively weak in both periods of falling and rising food prices, while the main rice-producing area (Sanjiang Plain) is less volatile, indicating its relatively strong agricultural economic resilience capacity. ③ Factors affecting agricultural economic resilience behave differently over the three cycles. During the period of rising international food prices, indicators reflecting agricultural production capacity have a greater impact on agricultural economic resilience, while during the period of falling international food prices, indicators reflecting agricultural input intensity and agricultural support capacity have a greater impact on agricultural economic resilience.